EKSISITENSI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN KUANTAN SINGINGI DALAM PEMBENTUKAN PERATURAN DAERAH - Firdaus, Emilda; ', Sapari; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Existence of Provincial Parliament as people's representative body area that has a very important role in the formation of local regulations. But in fact there has been no proposed Ranperda Parliament for Kuantan District Singingi establishment. Based on this understanding, the authors of this paper formulates three formulation of the problem, namely: first, What Role Legislative Council Singingi Regency Kuantan Formation of Regional Regulation? Secondly, Is constraints Legislative Council Kuantan District Singingi in the formation of regional regulation? Third, Is an attempt to overcome the problems of implementation of tasks Legislative Council Singingi Regency Kuantan in the formation of regional regulation?The method of this study, First, this type of research is legal and sociological research methods of data collection in the form of secondary legal literature that the data consisting of primary legal materials, secondary and tertiary. Second, the data collection techniques used in this study were interviews and questionnaires. Furthermore, the authors draw conclusions in this study using the deductive method of thinking, is to analyze the problems of the general form into specific shapes.From the research, there are three main problems that can be inferred, the first role of Parliament in the formation of local regulation has actually been going well, this is evidenced by the publication of a number of local regulations published by the Council with the executive, but in addition, it can be seen that less optimal right Singingi Kuantan District Council initiative to propose draft legislation, Second, obstacles still facing in Kuantan district legislature Singingi in the Legislative constrained in terms of human factors and lack of experience in the field of legislation invitation. Third, efforts to overcome the problems of implementation of tasks Legislative Council Singingi Kuantan district are: (1) Functions pegembangan Parliament, (2) Empowerment to Improve the Quality of Council Members, (3) Planning Institute of Parliament, and (4) Expert.Keywords: Existence - Parliament - Establishment of Regional Regulation